Dialektika nalar idealitas dan nalar realitas: aplikasi konsep umum al-balwa dalam dinamika hukum Islam - Firman Muhammad Arif (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
The application of law is not always oriented towards things that are ideal. There are certain other considerations or exceptions to the application of rules because they are beyond knowledge and no control. The general concept of umum al-balwa to fulﬁ ll interests including liminating difﬁ culties. By using qualitative descriptive analysis and considerations that are difﬁ cult to avoid or difﬁ cult to avoid become special considerations that result in dispensation. Cases that afﬂ ict human life are linked to other matters in various ﬁ elds with the niformity of considerations and the impact of giving relief which ends in making it easy but not easy.